Present-Day Patagonian Dust Emissions: Combining Surface Visibility, Mass Flux, and Reanalysis Data - Cosentino, Nicolas Juan; Gaiero, Diego Marcelo; Lambert, Fabrice (Journal of Geophysical Research: Atmospheres)
The magnitude of the climatic forcing associated with mineral dust aerosols remains uncertain due in part to a lack of observations on dust sources. While modeling and satellite studies provide spatially extensive constraints, they must be supported by surface-validating dust monitoring. Southern South America is the main dust source to the southern oceans (>45°S), a region of low biological productivity potentially susceptible to increased micronutrient fertilization through dust deposition, as well as one of the main dust sources to Antarctica, implying long-range transport of dust from Patagonia and potentially affecting snow cover albedo. We present multiyear time series of dust-related visibility reduction (DRVR) and dust mass flux in Patagonia. We find that local DRVR is partly controlled by long-term (i.e., months) water deficit, while same-day conditions play a smaller role, reflective of water retention properties of fine-grained dust-emitting soils in low-moisture conditions. This is supported independently by reanalysis data showing that large-scale dust outbreaks are usually associated with anomalously high long-term water deficit. By combining visibility data, surface dust sampling, and particle dispersion modeling, we derive regional dust emission rates. Our results suggest that the inclusion of long-term soil hydrologic balance parameterizations under low-moisture conditions may improve the performance of dust emission schemes in Earth system models. Fil: Cosentino, Nicolas Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina. Pontificia Universidad Católica de Chile; Chile Fil: Gaiero, Diego Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en ...